Prehospital End-Tidal CO2: A Superior Marker for Mortality Risk in the Acutely Injured Patient. Issue 8 (August 2022) - Willis, Robert G.; Cunningham, Kyle W.; Troia, Paola A.; Gutierrez, Ashley S.; Christmas, Ashley B.; Brintzenhoff, Rita; Sing, Ronald F.
Background: Emergency medical personnel must expeditiously triage acutely injured patients to the appropriate medical facility. Efficient and objective variables to facilitate this process and provide information to the receiving trauma center are needed. Currently, multiple variables are used to prognosticate injury severity and risk of mortality including vital signs, mental status, lactate, and base excess. We investigated the prehospital use of end-tidal carbon dioxide (ETCO2 ) as a noninvasive physiologic measure that can be obtained in the acutely injured patient. Methods: We performed a retrospective analysis of 557 acutely injured patients over 2 years at a Level 1 trauma center. All patients arriving as trauma activations with ETCO2 measurements were included in analysis. End-tidal carbon dioxide measurements were categorized as low, normal, and high based on reference levels. Mortality was the primary outcome. Secondary receiver operator curves (ROC) for base excess, venous lactate, blood pressure, and venous pH were compared. We hypothesized ETCO2 levels would be able to predict mortality. Results: End-tidal carbon dioxide levels conferred a mortality rate of 38%, 17.3%, and 2.9% for low, normal, and high, respectively ( P < .001). Receiver operator curve analysis produced an area under the curve predictive value for ETCO2 (.748) which was superior to lactate (.660), SBP (.578), pH (.560), and base excess (.497). Discussion: End-tidal carbon dioxide is a more sensitive and specific predictor of mortality in the acutely injured patient compared to venous lactate, base deficit, blood pressure, or venous pH. Additional studies are needed to determine if ETCO2 can be used as an effective prehospital adjunct to prevent mortality in acutely injured patients.